3D multichannel seismic reflection processed data (P-Cable system with GI Gun) of RV METEOR during cruise M154/1, Montserrat, Lesser Antilles - Michel Kühn; Christian Berndt; Sebastian Krastel (PANGAEA, 2023)
Included here are 3D post-stack time migrated data from Montserrat, Lesser Antilles. The data were collected aboard RV METEOR in 2019 during Research Cruise M154/1 using GEOMAR extquotesingles P-Cable seismic system. Seismic source were two Generator-Injector airguns fired in TRUE GI mode with generator and injector volumes of 105 cubic inches. The source was towed at a nominal depth of 2 m beneath the sea surface. Shot interval was 5 seconds at a ship speed of ~3.5 knots. Gun pressure was set at 160 bar. The receiver geometry consisted of 14 to 16 streamer sections attached to a 199 m long cross cable. Processing included: 3D geometry application, trace editing, static time corrections, anomalous amplitude attenuation, FK filtering, pre-stack trace interpolation, adaptive subtraction multiple suppression, sorting to common midpoint gathers, normal moveout correction (1580 m/s to 1725 m/s gradient velocity model), stacking, trace interpolation, 3D FK coherency filtering, 3D finite difference migration (1580 m/s to 1725 m/s gradient velocity model; first inline, then crossline). The dataset has a horizontal resolution of 3.125 m (bin size) and a dominant frequency of ~100 Hz.